Sapphire Photonic Crystal Waveguides with Integrated Bragg Grating Structure - Stefan Kefer; Gian-Luca Roth; Julian Zettl; Bernhard Schmauss; Ralf Hellmann (Photonics, 2022)
This contribution demonstrates photonic crystal waveguides generated within bulk planar sapphire substrates. A femtosecond laser is used to modify the refractive index in a hexagonal pattern around the pristine waveguide core. Near-field measurements reveal single-mode behavior at a wavelength of 1550 nm and the possibility to adapt the mode-field diameter. Based on far-field examinations, the effective refractive index contrast between the pristine waveguide core and depressed cladding is estimated to 3·10−4. Additionally, Bragg gratings are generated within the waveguide core. Due to the inherent birefringence of Al2O3, the gratings exhibit two distinct wavelengths of main reflection. Each reflection peak exhibits a narrow spectral full width at a half maximum of 130 pm and can be selectively addressed by exciting the birefringent waveguide with appropriately polarized light. Furthermore, a waveguide attenuation of 1 dB cm−1 is determined.